Dotacja budżetowa jako podstawowe źródło finansowania działalności uczelni publicznych w Polsce - Pisarska, Aleksandra; Wasilewski, Mirosław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
This study aims at the determination of sources of financing of operations of state-owned institutions of higher education in Poland. The source of empirical data was an announcement of the Minister for Science and Higher Education for years 2005 – concerning a list of institutions of higher education that received subsidies to the extent provided by relevant statutory regulations. The study offers a detailed analysis of legal regulations applicable to institutions of higher educations that govern their operations in all areas and provide a systematic review of sources of financing operations of institutions of higher education in Poland. A dominant source of financing operations of institutions of higher education is the state budget subsidy. That is why authorities of institutions of higher education make efforts in order to meet criteria that will result in the achievement of parameters that contribute to an increase in subsidy amounts in specific years. For all groups of institutions of higher education, an increase in subsidy amounts in the period under analysis (2005–2008) was determined. Institutions of higher education in the first group (universities) and fifth group (polytechnics) were in receipt of the largest subsidies. It reflects preferences in the relevant area in respect of entities that are most effective in terms of education and scientific research.